A Discourse on Sufis’ Approach to The Application of Ḥadīth - Gambari, Yusuph Dauda (Pascasarjana UIN Alauddin Makassar, 2024)
Ḥadīth, as the second primary source of Islam, is shrouded in many issues. Its application among the Sufis has attracted an array of attention. This is because they (Sufis) appear not to be in absolute compliance with the conventional methods of ḥadīth narration, authentication and application as put in place by Muḥaddithūn and widely used by scholars, especially the Salafiyyah. This study examines the Sufis’ approach to the usage and application of ḥadīth, especially their adherence to the rules of ḥadīth authentication. The analytical method of research is adopted in this study. It avails the opportunity to analyze various texts and scholars’ submissions on the science of ḥadīth as related to this study. It is discovered from this study that the Sufis, in most of their applications of ḥadīth, downplayed the rules as set by Muḥaddithūn due to their belief that the Prophet is still alive, even after his demise, and that direct link or connection with him is possible. So, they do not need stringent conditions to establish a report from the Prophet or act on it. It is also discovered that the bulk of narrations at the Sufis’ disposal are considered to be of weak or fabricated status. However, ḥadīth of the weak category can still be applicable in the realm of meritorious acts (faḍā’il), according to majority of the scholars. It is also discovered that some Sufis hold that as long as a particular narration does not contradict the principles of Islam, ascribing such to the Prophet should be less controversial. This s, therefore, concluded that Sufis flouted the rules of ḥadīth authentication with good intentions and attached importance to their propositions to make them gain wider acceptance from the people.